Actividad del interferón de tipo III contra el virus de la diarrea viral bovina - Quintana, María Eugenia (2019)
Bovine Viral Diarrhea Virus (BVDV) represents a major challenge at a productive level due to its endemic nature almost worldwide. BVDV infection is highly prevalent in Argentina,\ncausing economic losses for the dairy and livestock industry, mostly associated with reproductive problems. The disease caused by BVDV presents with a varied signology that can range from a subclinical course to acute hemorrhagic symptoms with usually fatal\noutcome. BVDV also causes immunosuppression that predisposes the infected animal to bacterial and parasitic infections.\nBVDV belongs to the Flaviviridae family, genus Pestivirus and is represented by 3\ngenotypes: VDVB-1, VDVB-2 and VDVB-3 or "HoBi-like virus". In turn, this agent can be classified according to its biotype in either cytopathic (CP) and non-cytopathic (NCP). A fundamental characteristic of VDVB is its ability to generate persistent infections. The birth\nof persistently infected animals (PI) occurs when the pregnant females become infected with\na NCP strain of the BVDV between days 30 and 150 of gestation. These individuals are not able to mount an immune response and eliminate large amounts of virus in all excretions\nand secretions. Currently, two main measures are proposed for the control of the disease: the detection and segregation of PI animals, and the subsequent vaccination of the entire\nnon-PI herd. The immunity conferred by vaccines that are on the market requires more than two weeks to develop and even more than one dose, moreover, its efficacy is non-optimal\nin the presence of maternal immunity. An additional disadvantage is that most of the commercial formulations do not provide\ncoverage against all virus strains circulating in the field. To complement the set of tools for VDVB control, antivirals are needed that can prevent viral\ndispersion, avoiding immunosuppression. Antivirals could be used in cases of outbreaks or\nas preventive before certain maneuvers such as transport, confinement, insemination, introduction of new animals, etc. In this work we propose the use of Interferons (IFNs) since\nthey are natural antivirals, of simple production and broad spectrum. In contrast to the\nadaptive immune response, the innate mechanisms of immune defense mediated by IFN are immediate and functional even in the early stages of intrauterine development. The\nadministration of IFNs as biotherapeutic agents is an effective measure for the treatment of several viral infections. Traditionally in therapies developed for humans, type I IFN (IFN-?)\nhas been used, which is currently being replaced due to its hematological toxicity, by type III IFN-?. IFN-?´s antitiviral effect is identical to IFN-? but localized in epithelia, without effect\non blood cells. The IFN-? family is conserved in cattle and treatment with IFN-?3 was successful in controlling oronasal infection with foot-and-mouth disease virus (FMDV). The therapeutic application or functionality of IFN-?3 to other viruses affecting livestock\nproduction has not been studied. This work proposes the following hypotheses: "Bovine IFN-?3 has antiviral activity against\nBVDV"; and "recombinant bovine IFN-?3 is a candidate to be used as a biotherapeutic agent\nagainst BVDV infections". To test these hypotheses, we have cloned and expressed the bovine INF-?3 and IFN-? in a recombinant system and evaluated their antiviral activity against different strains of BVDV both in vitro and in vivo to determine their potential use as\nbiotherapeutics.\nThe recombinant IFNs (rIFN) produced in supernatants of transfected HEK293T cells were quantified in active units determined on reference viruses and also using a reporter assay\nof activity based on Madin-Darby bovine kidney cells (MDBK) stably transfected with an MxA promoter upstream of the ORF for chloramphenicol acetyltransferase (CAT). To establish the sensitivity of VDVB field and reference strains to the rIFN, we developed a highthroughput technique applicable to CP and NPC strains. It is an in-cell ELISA that allows the\ndirect measurement of the infection by detecting a non-structural protein of the virus in cultured cell in microplates, without the need to harvest the cells. Using this assay, we\nestimated the 50% inhibitory concentration for each rINF using six strains of BVDV of\ndifferent biotype and genotype, verifying that the CP strains are more susceptible to both\nrIFN than the NCP and, particularly, the NCP type 2 strains were more sensitive to IFN-?. The activity of the rIFN was then evaluated in vivo, in a murine model of virulence developed\nin our laboratory, in which BALB/c mice infected with type 2 strains of the BVDV develop viremia at 4 or 7 days after infection. (dpi), according to the virulence of the strain. The high\nvirulence strain also suppressed the pro-inflammatory response in these animals. Treatment\nof mice with commercial murine rIFN showed that IFN-? would be more efficient in preventing infection while IFN-? would prevent viremia. Experiments of combined treatment with two doses of antiviral pre-and post-infection, combining the use of both rIFN, revealed\nthat the treatment with IFN-? before the infection followed then by IFN-? was effective in controlling the viremia in the mice, and that a pre- and post-infection treatment with IFN-? was equally protective. These results then indicated that rIFN-? was effective against BVDV\nin vivo, and that it would not be necessary to combine it with IFN-?. In order to evaluate the use of our rIFNs in cattle, we first established their safety on bovine blood cells (ex vivo). Both rIFNs were safe at the proposed usage doses, despite the fact that IFN-? caused apoptosis of immune cells when tested in very high doses. Safety studies\nwere carried out directly in the animals by assessing several hematological parameters postinoculation, with satisfactory results. We then performed a proof-of-concept experiment in\ncalves to evaluate the antiviral activity of rIFN-? against infection with an Argentinean field\nstrain (genotype 2, NCP) isolated in Buenos Aires province, which had been extensively characterized in our laboratory. Six BVDV free calves, which were infected with the above\nstrain, were selected for the study. Four of them were inoculated subcutaneously with two doses of rIFN-? two days before infection and two days after infection, while the other two\ncalves received placebo treatment (dilution medium). The untreated-infected animals developed clinical signs of respiratory disease between 2 and 4 days post-infection, viremia and viral excretion through nasal secretions were also detected. All the animals of the RIFN? treated group did not develop disease, none of them showed clinical signs. Three of them did not even present viremia or shedding.\nOnly one individual of the latter group presented viremia and shedding with lower values than those of the untreated group.\nWe have developed a recombinant IFN-?, a safe and effective antiviral, and demonstrated its potential use for the prevention and treatment of BVDV infections. We verified its antiviral effect against field and reference strains in vitro, as well as its innocuity and efficacy in cattle against an Argentinean field strain. We have established the BVDV mouse model of viremia which is very useful for studies with this virus in vivo. We developed a novel technique, consisting of an In-cell ELISA that uses a detector antibody against a conserved nonstructural protein that can be potentially applicable to accurately measure the infectivity of any viral strain, regardless of its ability to cause cell death in culture.\nThis work constitutes the first experimental evidence of the activity of bovine IFN-? as a biotherapeutic tool against BVDV in vivo, opening a new perspective focused on the use of\neconomic, biodegradable and safe biological antivirals to reduce the incidence of viral infections in animals in productive environment .\nThe application of this tool could indirectly impact the decrease in the use of antibiotics by decreasing the rate of bacterial infections that result from immune-suppressive viral infections.